PENGARUH AUDIT TENURE, FIRM SIZE DAN FIRM AGE TERHADAP AUDIT DELAY - Susilo, Bambang Widjanarko; Rokhman, Nur; Kusumajaya, Robby Andika; Saidah, Nur (Dinamika: Jurnal Manajemen Sosial Ekonomi, 2024)
The purpose of this study is to determine the effect of audit tenure, firm size and firm age on audit delay. The research covers 48 real estate companies on the Indonesia Stock Exchange from 2019 to 2021, purposive sampling techniques. By using the SPSS v24 tool to perform multiple linear regression analysis. The statistical results obtained by the tenure audit and the size of the company are not significant factors affecting the audit delay. Only the age of the company is significant on the audit delay